UNIT 11.2 Submitting a Sequence to GenBank. Issue 12 (2nd May 2016) - Chang, Wei‐Jen; Zaila, Kassandra E.; Coppola, Thomas W.
Abstract : In the post‐genomic era, more and more research projects involve the generation of molecular sequence data. How should these newly obtained DNA/protein sequences be analyzed, and how should they be prepared for submission to sequence databases? In this unit, we provide guidelines and a flowchart to help first‐time users process new sequence data using third‐party freeware programs and give a step‐by‐step demonstration on the preparation of a sequence file for submission to GenBank using the Sequin program. © 2016 by John Wiley & Sons, Inc.